Critical Thinking in Undergraduate Students' Analytical Writing - Ajeng Setyorini; Faiza Hawa (Journal of English Language Learning, 2024)
The aim of this study is to investigate how undergraduate students exercise their critical thinking skills through the phrasing and sentence structure of their analytical writing. This research investigates how students translate their critical faculties into the linguistic choices and rhetorical techniques employed in their written analytical texts. In particular, it has investigated how students engage with critical argument and logic through the phrasing, sentence structure, and text structuring of their writing, as well as the linguistic and rhetorical resources used to communicate processes and outcomes of their thinking. This set of research questions is framed to allow the investigation into the relationship between critical thinking and written expression, whereby it hopes to gain insight into the way students can bridge such a gap in academic writing. The findings will enable pedagogical approaches toward the empowerment of students for better clarity and persuasiveness in communicating their ideas and reasoning.